DEVELOPMENT OF A DYNAMIC SIMULATOR FOR DOUBLE-EFFECT COMMERCIAL STEAM ABSORPTION CHILLER - SALIH AHMED, MOJAHID SIDAHMED MOHAMMED (2014)
In spite of the great e!Torts that have been made to improve the efficiency of air conditioning systems, the energy consumption for air conditioning has kept on increasing. The demand for energy conservation has increased significantly. In order to address these, there are increasing needs for research and development on absorption chillers including reliability enhancement, energy saving control, and the performance degradation identification. To find out the performance of absorption chiller at the early development stage, experimental tests of prototypes of the chiller were the only available method. Since absorption chiller of large capacity requires huge power, the development of coefficient of performance (COP) and control performance requires expensive test facilities, considerable time and cost. Therefore, it is necessary to reduce the inefficiencies by applying a mathematical simulation model using computational techniques.